1997
DOI: 10.1002/j.1551-8833.1997.tb08198.x
|View full text |Cite
|
Sign up to set email alerts
|

Surveying arsenic occurrence

Abstract: Data from US arsenic occurrence surveys are used to estimate compliance violations given a range of possible arsenic standards. Three surveys of arsenic occurrence in US drinking water supplies were synthesized to estimate how possible arsenic standards would affect compliance. Detectable levels of arsenic (0.5 μg/L) were found in 73 percent of surface water sources and 58 percent of groundwater sources. For finished water, detectable arsenic occurred in 45 percent of surface water systems and 53 percent of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 15 publications
(14 reference statements)
1
49
0
Order By: Relevance
“…Arsenic also was frequently detected in previous studies. For example, arsenic concentrations greater than or equal to 0.5 µg/L were detected in 58 percent of groundwater sources in United States drinking-water supplies in the National Arsenic Occurrence Survey (Frey and Edwards, 1997). Arsenic concentrations were greater than the MCL of 10 µg/L (U.S. Environmental Protection Agency, 2006a) in about 10 percent of source-water samples in this study (table 11) (Nordstrom, 2002).…”
Section: Arsenicmentioning
confidence: 52%
See 1 more Smart Citation
“…Arsenic also was frequently detected in previous studies. For example, arsenic concentrations greater than or equal to 0.5 µg/L were detected in 58 percent of groundwater sources in United States drinking-water supplies in the National Arsenic Occurrence Survey (Frey and Edwards, 1997). Arsenic concentrations were greater than the MCL of 10 µg/L (U.S. Environmental Protection Agency, 2006a) in about 10 percent of source-water samples in this study (table 11) (Nordstrom, 2002).…”
Section: Arsenicmentioning
confidence: 52%
“…Arsenic concentrations greater than the MCL were detected in public-well samples from all system sizes, but about one-half of the samples with arsenic concentrations greater than the MCL were collected from large and very large systems (data not shown). Similarly, Frey and Edwards (1997) reported that arsenic concentrations were highest in large groundwater-supplied public water systems serving more than 10,000 people. System size may be related to multiple factors, such as well capacity (pumping rate), groundwater contributing area, usage patterns, and well drilling and maintenance practices.…”
Section: Arsenicmentioning
confidence: 99%
“…The NAOS study (Frey and Edwards 1997) found that most drinking water supplies are already at arsenic levels of 2 to 3 µg/ L, which results in an exposure of 2.2 to 3.3 µg/day assuming a daily intake of 1.1 L tap water. We estimate that food and drinking water are the major contributors to inorganic arsenic exposure, with food contributing slightly more than water.…”
Section: Resultsmentioning
confidence: 99%
“…For the present probabilistic model, all arsenic in drinking water is assumed to be inorganic. Levels of arsenic in drinking water sources in the U.S. were analyzed in the National Arsenic Occurrence Survey (NAOS) (Frey and Edwards 1997). Arsenic in the water samples was measured by inductively coupled plasma-mass spectroscopy, and the quantitation limit was 0.5 µg/L.…”
Section: Watermentioning
confidence: 99%
See 1 more Smart Citation